Study on Multi-objective Location of Distribution Center Based on Covering - SUN Lin; WU Xiang_lin; LIU Yue; SUN Yong_Zhe; QU Hui (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Distribution center is an important part of modern logistics system. In the process of designing distribution center, running expense can be greatly reduced by selecting appropriate location of distribution center. In this paper, the covering method was used twice to choose the distribution center and minimize the total cost. At last, a case was given to test the model. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1915